CEO’s Financial Literacy and Technological Innovation: The Role of Risk Taking and Management Control Systems - Nuraini, Siti; Fikri, Muhammad Ali; Ferdy, Ferdy; Sulistiyani, Tina; Rini, Poppy Laksita (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study investigates how CEO financial literacy influences technological innovation in Indonesian MSMEs, with risk-taking and management control systems (MCS) as sequential mediators. The key contribution lies in advancing a dual-path mediation model that links individual financial competence to organizational innovation in emerging market contexts. Using PLS-SEM on data from 113 MSME CEOs across Java, findings reveal that CEO financial literacy directly promotes innovation, while risk-taking alone does not mediate this effect. However, MCS significantly mediates the relationship, and both variables jointly form a significant sequential path. These results highlight the importance of CEO financial literacy not only as a strategic resource but as a driver of internal capability development. For managers and policymakers, the findings emphasize that financial literacy must be paired with robust internal control systems to accelerate innovation and long-term competitiveness in MSMEs.